Do parties represent the people? Left-right party congruence across Europe - Belchior, Ana Maria (Portuguese Journal of Social Science, 2011)
How ideologically congruent are deputies and voters within European political parties? And which variables best explain left-right party congruence? These are the main questions in this article, which connect to two objectives: describing the left-right congruence situation generated by European political parties, providing an individual characterization of deputy-voter’s congruence; and providing an explanation that helps account for parties’ ideological congruence. The article aims to empirically update previous research. Supported by data from the European Representation Studies, it includes political parties from 11 European countries in the sample. The findings reveal that, in respect to the first goal, ideological congruence is more or less similar across countries and parties, showing in particular that the left-wing does not exhibit higher levels of congruence. On the second goal, it was found that deputies’ ideological position on the right-wing appears to be the most important explanatory variable for left-right party congruence.